Ice motion measurements, south-west Greenland Ice Sheet (version 2) - Tedstone, Andrew; Neinow, Peter (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2018)
From May 2009 to May 2013, seven dual-frequency GPS receivers were deployed along a 120 km-long transect in the south-west of the Greenland Ice Sheet. Two additional dual-frequency GPS receivers were deployed perpendicular to longitudinal ice flow at ~14 km inland: one 5 km distant from June 2011 to May 2013, and another 2.5 km distance from May 2012 to May 2013. Each receiver recorded position observations every 10 seconds or 30 seconds (depending on configuration), enabling resolution of horizontal and vertical ice motion. Sites were powered by solar panels and operated 24 hours a day during summer but shut down in the autumn. Absolute ice displacements at each site were obtained for each summer and winter period in the absence of continuous measurements. Position measurements were kinematically corrected relative to an off-ice base station using TRACK (Chen, 1999). Daily velocities were then obtained by differencing across 24-hour periods, whilst continuous velocities were obtained through application of a sliding 6-hour differencing window. At each GPS site we also measured (1) the near-surface air temperature every 15 minutes year-round, (2) net seasonal ablation using ablation stakes, and (3) at several selected sites melt rates using sonic ranging sensors. This version 2 of the dataset updates the previously 2-day temporal resolution of the ice motion records to 1-day resolution. In other respects the dataset has not changed.